PEMIKIRAN EPISTEMOLOGI AMIN ABDULLAH DAN RELEVANSINYA BAGI PENDIDIKAN TINGGI DI INDONESIA - Waston Waston (Profetika: Jurnal Studi Islam, 2016)
The relation between religion and science seems to be the dichotomous view. Bothof them are like oil and water, two entities that cannot be reunited and separated. Due to “thisdispute”, science often misses their ethics, so science and modern technology have actuallyhumanized humans and distanced them from their nature. The conflict between them forcesmany intellectual Muslims to make “epistemology bridge” for reconciling science and religion.One of them is M. Amin Abdullah, who argues with the concept of integration-interconnectionwhich is the effort to avoid the dichotomous view of the science and religion (especiallyIslam-science) and in the epistemology view, the concept is to close back all disciplines so thereare dialogues, communications, relationships, and mutual help. This article aims to discussthe epistemology thought of M. Amin Abdullah concerning on integration-interconnectionwith its methodology and relevance for the scientific development of higher education in Indonesia.Keywords: Epistemology; Islam; science; Integration-interconnection.Abstrak: Hubungan antara agama dan ilmu pengetahuan tampaknya menjadi pandangandikotomis. Keduanya ibarat minyak dan air, dua entitas yang tidak bisa bersatu kembali dandipisahkan. Karena “sengketa ini” ilmu pengetahuan mencoba merangkul konsep-konsep agamadan etika agar ilmu pengetahuan-teknologi memiliki nuansa yang manusiawi. Konflikantara keduanya memaksa kaum Muslim intelektual membuat “jembatan epistemologi” untukmendamaikan sains dan agama. Salah satunya adalah M. Amin Abdullah, yang berpendapatbahwa konsep integrasi-interkoneksi yang merupakan upaya untuk menghindari pandangandikotomis dari ilmu dan agama (khususnya Islam-ilmu) dan dalam pandangan epistemologi,konsep ini mencoba menawarkan kembali semua disiplin ilmu sehingga ada dialogisasi, komunikasi,sinergitas, dan hubungan saling membantu. Artikel ini bertujuan untuk membahasepistemologi pemikiran M. Amin Abdullah berkenaan konsep integrasi-interkoneksi denganmetodologi dan relevansinya bagi pengembangan ilmu pengetahuan pendidikan tinggi di Indonesia.Kata kunci: Epistemologi; Islam; ilmu pengetahuan; Integrasi-interkoneksi.